Combination of Lurbinectedin and Osimertinib for Treatment of EGFR-Mutated Transformed SCLC: A Brief Report - Aditi Singh, MBBS, MPH; Arthi Sridhar, MBBS; Aastha Poddar, MBBS; Anastasios Dimou, MD; Kaushal Parikh, MBBS; Mohamed Shanshal, MD; Anna Schwecke, APRN, CNP, MS; Nicole Moffett, APRN, CNP, MSN; Manish R. Patel, DO; Aaron S. Mansfield, MD; Konstantinos Leventakos, MD, PhD (JTO Clinical and Research Reports)
Third-generation tyrosine kinase inhibitors are effective treatment of EGFR-mutated NSCLC. After an initial response, patients on this therapy ultimately develop resistance leading to disease progression. One of the resistance mechanisms is histological transformation to SCLC. There is no standard of care for the management of transformed SCLC. Given the rarity of transformed SCLC, it is important to study treatment options that are safe and effective for this disease. In this case series, three patients received treatment with lurbinectedin plus osimertinib after transformation to SCLC. In our limited experience, the combination was found to be safe.